2017
DOI: 10.1155/2017/7307618
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sarcopenic Obesity in Adults with Class II/III Obesity Using Different Diagnostic Criteria

Abstract: Background/Objective. Sarcopenic obesity (SO) is a hidden condition of reduced lean soft tissue (LST) in context of excess adiposity. SO is most commonly reported in older adults and both its risk and prevalence increase with age. A variety of body composition indices and cut points have been used to define this condition, leading to conflicting prevalence and risk prediction. Here, we investigate variability in the prevalence of SO in an adult sample of individuals with class II/III obesity (BMI ≥ 35 kg/m2) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 41 publications
7
55
0
1
Order By: Relevance
“…Firstly, our assessment of the prevalence of sarcopenia among patients with obesity seeking treatment, using criteria accounting for body weight, revealed an SO prevalence of 49.5% across the entire sample (53.1% in males and 48.1% in females). This falls within the large prevalence range of 0-100% reported for males and 0-85% reported for females, a range that may depend on the SO definition applied (24), in which a greater prevalence may be likely to be reported in studies accounting for body weight or BMI, whereas a smaller prevalence will be reported in those that do not (16). However, specifically, the prevalence of sarcopenia in our sample (53.1% in males and 48.1% in females) highly exceeded that found by Oh and colleagues in their original sample (19.6% in males and 31.3% in females) (18).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Firstly, our assessment of the prevalence of sarcopenia among patients with obesity seeking treatment, using criteria accounting for body weight, revealed an SO prevalence of 49.5% across the entire sample (53.1% in males and 48.1% in females). This falls within the large prevalence range of 0-100% reported for males and 0-85% reported for females, a range that may depend on the SO definition applied (24), in which a greater prevalence may be likely to be reported in studies accounting for body weight or BMI, whereas a smaller prevalence will be reported in those that do not (16). However, specifically, the prevalence of sarcopenia in our sample (53.1% in males and 48.1% in females) highly exceeded that found by Oh and colleagues in their original sample (19.6% in males and 31.3% in females) (18).…”
Section: Discussionsupporting
confidence: 58%
“…Firstly, patients with obesity tend to have a relatively large lean mass (15). Hence, sarcopenia criteria may not be met in these individuals, and the prevalence of sarcopenia may be underestimated (16). Second, low physical fitness is more closely associated with obesity than sarcopenia (17).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, patients with obesity tend to have a relatively large lean mass. Hence, sarcopenia criteria based on this parameter may not be met in these individuals and the prevalence of sarcopenia may, therefore, be greatly underestimated [8]. Secondly, low physical fitness is more strongly associated with obesity than with sarcopenia [9], with the result that the prevalence of sarcopenia may be overestimated.…”
Section: Definition Of Sarcopenic Obesitymentioning
confidence: 99%
“…To address this problem, recent reports have recommended accounting for body mass or body fat mass when identifying individuals with sarcopenic obesity [8]. In light of this recommendation, a new definition of sarcopenic obesity has been established, which in addition to the Appendicular Lean Mass (ALM) also includes the Body Mass Index (BMI) [10].…”
Section: Definition Of Sarcopenic Obesitymentioning
confidence: 99%
“…Different approaches such as the ratio of appendicular skeletal muscle mass and height squared (aLM/ht²) has been widely used 2 . In addition, based on the literature review, ten studies used the aLM to define sarcopenia 3 . However, this approach requires further refinement as it was based in a small and unknown representative population of the Rosetta Study 2 .…”
Section: Introductionmentioning
confidence: 99%